Liver Function Test (SGPT) Abnormality in 319 Confirmed COVID-19 Cases in Bangladesh (Bangladesh Journal of Medicine, 2023)
Background: Deranged liver function abnormalities are well-recognized sequela of COVID-19 infection. Globally, there are studies dedicated to evaluate spectrum of liver injury by COVID-19. In this study, we have described the impact of COVID-19 on liver function tests in 319 confirmed COVID cases. Our study aimed to evaluate the liver function alteration by COVID-19 in our population.Methods: This study included all adult inpatients (> 18 years old) with laboratory confirmed (RT-PCR) COVID-19 from March to April, 2020 in a tertiary COVID dedicated hospital. We assessed liver function test and categorized patients according to COVID severity. This was a single center, retrospective, observational study.Results: Among 319 patients with COVID-19, 36% had normal and 64% had abnormal liver function test. Out of this, 18% had 1-2 times, 42% had 2-3 times and 19% had >3 times upper limit of normal SGPT during admission. 57 (18%) patients presented with mild illness, 83 (26%) with moderate, 124 (39%) patients with severe and 54 (17%) with critical COVID-19 during admission. Significant correlation was found between severity of COVID-19 and raised SGPT level.Conclusion: More than half of patients presented during admission with abnormal liver function. COVID-19 has significant impact on liver function derangement in this population.Bangladesh J Medicine 2023; Vol. 34, No. 2(1) Supplement: 217